The Role of Antiapoptotic Erythropoietin on Ultraviolet B-Induced Photodamaged Skin Through Inhibition of Sunburn Cells - Suyono, Handi; Sanjaya, Kristian; Susanti, Deby (Folia Medica Indonesiana, 2020)
Ultraviolet light causes photodamaged skin leading to photoaging skin. Ultraviolet-B (UV-B) causes epidermal keratinocyte apoptosis, namely sunburn cell, through apoptotic intrinsic pathway. Erythropoietin (EPO) has a role in cytoprotection in various tissues but its role to epidermal skin is not clear yet. This study was designed pretest-posttest control group design. Thirty two male mice Mus musculus, strain Balbc, were divided into control and treatment group, 16 mice each group. All mice were exposured by UV-B light 16mJ/cm2, distance 30 cm, duration 90 seconds, for 3 consecutive days. Four mice each group were randomly sacrificed as pretest data. The control mice were given aquadest subcutaneous injection 0.1 mL, and treatment mice were given EPO subcutaneous injection 0.1 mL (100 IU/kg BW). UVB were given everyday with same protocol above. Treatments were given 4 times, interval 3 days. All mice were sacrificed to examine sunburn cells. Data were performed as mean ± SD and analyzed by t-test using SPSS 17.0 with significant value p<0.05. Sunburn cells of pretest control were 25.00 ± 4.85% and treatment group were 24.83 ± 5.15%. Sunburn cells significantly decreased (p=0.002) in treatment group (31.5 ± 9.39%) than control (50.83 ± 6.70%). UV-B causes sunburn cells formation. EPO inhibits apoptosis through increasing NO production and eNOS expression, inhibiting caspase and proinflammatory cytokines, and increasing antiapoptotic protein. EPO has a role in skin apoptosis inhibition which is shown by decreased sunburn cells